2012
DOI: 10.1371/journal.pone.0038132
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographic Analysis Elucidates the Influence of the Ice Ages on the Disjunct Distribution of Relict Dragonflies in Asia

Abstract: Unusual biogeographic patterns of closely related groups reflect events in the past, and molecular analyses can help to elucidate these events. While ample research on the origin of disjunct distributions of different organism groups in the Western Paleartic has been conducted, such studies are rare for Eastern Palearctic organisms. In this paper we present a phylogeographic analysis of the disjunct distribution pattern of the extant species of the strongly cool-adapted Epiophlebia dragonflies from Asia. We in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 28 publications
3
24
0
Order By: Relevance
“…For establishing our homology hypotheses we supplemented our data with information from the literature [7], [10], [14], [17], focusing on Asahina’s comprehencive study of Epiophlebia superstes [7], which represents a conspicuous mixture of anisopteran and zygopteran characters [4], [7], [20], [21]. Furthermore, in many aspects Epiophlebia seems to have the most ancestral character distribution within the Odonata (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…For establishing our homology hypotheses we supplemented our data with information from the literature [7], [10], [14], [17], focusing on Asahina’s comprehencive study of Epiophlebia superstes [7], which represents a conspicuous mixture of anisopteran and zygopteran characters [4], [7], [20], [21]. Furthermore, in many aspects Epiophlebia seems to have the most ancestral character distribution within the Odonata (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…29. A third and fourth species of Epiophlebia were described recently from China based on limited evidence (Carle 2012;Li et al 2012), especially in the light of negligible genetic variation found in three of the species (Büsse et al 2012). 30.…”
Section: Classificationmentioning
confidence: 99%
“…Almost all known recent Odonata can be assigned to one of two groups: either to the Anisoptera (dragonflies) or to the Zygoptera (damselflies). A conspicuous exception are the few species of Epiophlebia , which combine characteristics of both groups 1 2 . Epiophlebia nymphs resemble those of the Anisoptera, respiring through a rectal chamber, while lacking the paddle shaped gills that arise from the tip of the abdomen 1 and are characteristic of Zygoptera.…”
mentioning
confidence: 99%